Enhancing nurses’ competence in mechanical ventilation: a quasi-experimental study and its association with patient severity using APACHE II - Noha Mohammed Ibrahim; Samia Eaid Elgazzar; Amany Ibrahim Ezz Eldin; Abdo Mansoor Alhusami; Mona Metwally El-Sayed; Mohamed Goda Elbqry; Fatma Mohamed Elmansy; Shereen Ahmed A. Qalawa; Nasiru Mohammed Abdullahi; Saddam Ahmed Al-Ahdal; Hanadi Dakhilallah; Sheren Ebrahim El-Hag El-Tahry (Frontiers in Medicine, 2026)
Background Mechanical ventilation is a cornerstone of intensive care, requiring ICU nurses to have adequate knowledge, competence, and skills to provide safe, evidence-based care. Although educational programs improve nurses’ preparedness, evidence of their impact on patient outcomes remains limited. Aim To assess ICU nurses’ knowledge, professional competence, and clinical practice related to mechanical ventilation following participation in a structured educational program, and to explore the association between nursing competence and patient severity as measured by APACHE II scores. Methods A quasi-experimental study design was conducted in the Egyptian Health Care Authority Hospitals in Port Said Governorate. A convenience sample was used. The study involved one group of ICU nurses evaluated pre- and post-educational program, and two separate cohorts of mechanically ventilated patients (50 each) admitted before and after intervention. Nurses and patients were not paired, and patient cohorts differed in case-mix profiles. Four validated assessment tools were utilized to measure nurses’ knowledge, competence, clinical skills & patients’ demographic and clinical data. Results ICU nurses demonstrated significantly higher post-training scores in knowledge, professional competence, and clinical performance compared with their pre-training scores ( p < 0.001). Moreover, a substantial contrast in APACHE II scores was noted between patient groups before and after the intervention ( p < 0.001). Nevertheless, given that APACHE II evaluates the severity of illness upon ICU admission within the initial 24 h and the patient cohorts were distinct, the observed difference is more likely due to diversities in case complexity rather than an impact directly linked to the educational program. Conclusion Participation in the educational program was associated with higher immediate post-training scores in ICU nurses’ knowledge, professional competence, and clinical performance. The APACHE II scores of the pre- and post-intervention patient cohorts differed; however, this does not prove that the educational program had a direct impact on patient outcomes. Further multicenter studies with controlled designs are needed to better evaluate the relationship between educational interventions and patient outcomes.